Referral of children seeking care at private health facilities in Uganda. (December 2017) - Mbonye, Anthony; Buregyeya, Esther; Rutebemberwa, Elizeus; Clarke, Siân; Lal, Sham; Hansen, Kristian; Magnussen, Pascal; LaRussa, Philip
Abstract Background In Uganda, referral of sick children seeking care at public health facilities is poor and widely reported. However, studies focusing on the private health sector are scanty. The main objective of this study was to assess referral practices for sick children seeking care at private health facilities in order to explore ways of improving treatment and referral of sick children in this sector. Methods A survey was conducted from August to October 2014 in Mukono district, central Uganda. Data was collected using a structured questionnaire supplemented by Focus Group Discussions and Key Informant interviews with private providers and community members. Results A total of 241 private health facilities were surveyed; 170 (70.5%) were registered drug shops, 59 (24.5%) private clinics and 12 (5.0%) pharmacies. Overall, 104/241 (43.2%) of the private health facilities reported that they had referred sick children to higher levels of care in the two weeks prior to the survey. The main constraints to follow referral advice as perceived by caretakers were: not appreciating the importance of referral, gender-related decision-making and negotiations at household level, poor quality of care at referral facilities, inadequate finances at household level; while the perception that referral leads to loss of prestige and profit was a major constraint to private providers. Conclusion In conclusion, the results show that referral of sick children at private health facilities faces many challenges at provider, caretaker, household and community levels. Thus, interventions to address constraints to referral of sick children are urgently needed.